2015
DOI: 10.1210/me.2014-1363
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Progesterone Receptor A and B Isoforms During Human Endometrial Decidualization

Abstract: Progesterone, acting through the progesterone receptors (PGRs), is one of the most critical regulators of endometrial differentiation, known as decidualization, which is a key step toward the establishment of pregnancy. Yet a long-standing unresolved issue in uterine biology is the precise roles played by the major PGR isoforms, PGR-A and PGR-B, during decidualization in the human. Our approach, expressing PGR-A and PGR-B individually after silencing endogenous PGRs in human endometrial stromal cells (HESCs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 54 publications
5
58
0
1
Order By: Relevance
“…Analysis of the RNA-seq data using DESeq2 24 revealed 1,135 differentially expressed genes after decidualization (Table 1). Genes with decreased expression after 48 hours of treatment were highly enriched for cell cycle genes (Supplementary File S2), consistent with observations from endometrial biopsies from non-pregnant women that decidualization is associated with cell cycle arrest 18,25 . Genes with increased expression after treatment were enriched for insulin-related terms, also consistent with previous results from endometrial biopsies 25 , and for glucose metabolism 17 .…”
Section: Robust Gene Expression Changes Occur In Decidualized Stromalsupporting
confidence: 85%
“…Analysis of the RNA-seq data using DESeq2 24 revealed 1,135 differentially expressed genes after decidualization (Table 1). Genes with decreased expression after 48 hours of treatment were highly enriched for cell cycle genes (Supplementary File S2), consistent with observations from endometrial biopsies from non-pregnant women that decidualization is associated with cell cycle arrest 18,25 . Genes with increased expression after treatment were enriched for insulin-related terms, also consistent with previous results from endometrial biopsies 25 , and for glucose metabolism 17 .…”
Section: Robust Gene Expression Changes Occur In Decidualized Stromalsupporting
confidence: 85%
“…The progesterone receptor gene (PGR) encodes two well-characterized isoforms (PR-A and PR-B) that are transcribed from distinct promoters and utilize different translation start sites in the first exon, but are identical except for a 165 amino acid trans-activation domain in the amino terminus of PR-B (Kastner et al 1990). Consistent with the structural differences between PR-A and PR-B, previous studies have shown that PR-B is a stronger trans-activator of progesterone responsive genes than PR-A, whereas PR-A acts as a dominant trans-repressor of PR-B mediated trans-activation (Kastner et al 1990;Huse et al 1998;Giangrande et al 2000;Abdel-Hafiz et al 2002;Kaya et al 2015). These opposing transcriptional activities result from different post-translational modifications and cofactor interactions.…”
Section: Introductionsupporting
confidence: 62%
“…By contrast, we noted comparable endometrial expression levels of PR and E6AP in both groups (Figure 7, A, D, and E). These aberrantly lower expression levels of BMI1, but not PR and E6AP, in failed pregnancy were well associated with reduced expression levels of PR-target genes including FOSL2, JUN, TGFB1, and IRS (18,19,23) (Figure 7F), indicating a close correlation between BMI1 and P4-PR nuclear signaling in human endometrium during early pregnancy.…”
Section: Discussionmentioning
confidence: 90%